2020
DOI: 10.1007/s00170-020-05608-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic force modelling in drilling of AFRP composite considering the chisel edge extrusion

Abstract: Aramid fiber reinforced plastic (AFRP) composites have been widely used in automotive, aerospace, and defense industries. The common AFRP drilling process tends to cause damage to the composite structures which subsequently affects their fatigue lives and in-service performance. Understanding the mechanism of cutting forces generation is crucial in controlling the cutting process for achieving desired hole quality and machining accuracy. This study proposes a novel mechanistic model considering both the cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…As the case in hand at speed 400 rpm, feed 0.2 mm/r and thickness of 2.6 mm, the variation in drill point angle from 100° to 118° to 140°, and the delamination factor increased from 1.49 to 1.53 to 1.62, respectively. The same observation has been reported [ 4 , 41 ]. It is also noted that the delamination factor is proportional to feed and speed.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…As the case in hand at speed 400 rpm, feed 0.2 mm/r and thickness of 2.6 mm, the variation in drill point angle from 100° to 118° to 140°, and the delamination factor increased from 1.49 to 1.53 to 1.62, respectively. The same observation has been reported [ 4 , 41 ]. It is also noted that the delamination factor is proportional to feed and speed.…”
Section: Methodssupporting
confidence: 89%
“…Bayraktar and Turgut [ 4 ] presented the influence of drill point angle on delamination of C/C/Al 6013-T651 stacks with uncoated and coated drills and concluded that uncoated drill has better performance than coated drill according to delamination criterion. Liu et al [ 41 ] proved that the thrust force produced by extrusion of the chisel edge is greater than that generated by cutting the chisel edge. Shu et al [ 42 ] conducted a comprehensive comparison between the dedicated and conventional drill bit designs from various views, such as thermal, mechanical, and chip formation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to restrain the delamination damage, it has great significance to predict the thrust force at the beginning of the delamination and to control the thrust force during the drilling process. The total thrust force is divided into three components in the drilling of polymer composite materials: (i) thrust force generated by the cutting lips; (ii) thrust force generated by the chisel edge cutting action; (iii) extrusion force generated by the chisel edge extrusion action [47]. Figure 8 illustrates the effects of the number of holes drilled on the thrust force.…”
Section: Thrust Forcementioning
confidence: 99%
“…To date, drilling is still considered as the most pivotal hole-making process in composite component assemblies due to its cost effectiveness [2]. However, drilling of AFRP remains a challenge due to the inherent anisotropic multiphase structure of the material [3]. Drilling-induced damages, such as thermal degradation, fiber bundle tearing, and delamination, are common in the AFRP hole making processes.…”
Section: Introductionmentioning
confidence: 99%